Consumers’ Perception Towards Green Products in Nepal - Thapa, Gopal (NCC Journal, 2019)
The concept of green products is not very old in Nepal. This research paper is an endeavor to examine consumer level of awareness and perception towards green products in Nepal. The data has been collected from a total of 192 respondents in Kathmandu through well-structured questionnaire. An increasing number of consumers have adequate knowledge about green products features, majority of them view green products as healthy and safe. Consumers prefer to believe that green products are offering high quality over conventional products, but they are not having any precise opinion about the excessive prices of green products. The research results also find out consumers’ disappointment towards the promotional measures taken by the marketer. This research will be a good cognizance for the marketers and will increase their seriousness to focus more on making consumer more aware about green products benefits and bring about the adoption of green products.